2021
DOI: 10.3390/molecules26185477
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Preparation of Chiral Stationary Phases: Progress on Coating and Immobilization Methods

Abstract: Enantioselective chromatography is one of the most used techniques for the separation and purification of enantiomers. The most important issue for a specific successful enantioseparation is the selection of the suitable chiral stationary phase (CSP). Different synthetic approaches have been applied for the preparation of CSPs, which embrace coating and immobilization methods. In addition to the classical and broadly applied coating and immobilization procedures, innovating strategies have been introduced rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Over the years, different synthetic approaches have been applied for preparation of CSPs, which embrace coating and immobilization methods. In addition to the classical and broadly applied coating and immobilization procedures, innovating strategies have been introduced [128]. The approaches applied for preparation of the homemade columns to perform the binding affinity studies shown in Table 4 were diverse, in which HSA was immobilized [111,112,123], adsorbed [113] or entrapped [125] on the chromatographic support.…”
Section: Zonal Analysismentioning
confidence: 99%
“…Over the years, different synthetic approaches have been applied for preparation of CSPs, which embrace coating and immobilization methods. In addition to the classical and broadly applied coating and immobilization procedures, innovating strategies have been introduced [128]. The approaches applied for preparation of the homemade columns to perform the binding affinity studies shown in Table 4 were diverse, in which HSA was immobilized [111,112,123], adsorbed [113] or entrapped [125] on the chromatographic support.…”
Section: Zonal Analysismentioning
confidence: 99%
“…Immobilization of CSPs, i.e., covalent chemical linkage of cellulose derivative-based CSs onto prefunctionalized silica gel, is thus the most obvious and suitable option to overcome the shortcomings of its "coated-only" counterparts, and their inherent problems with the dissolution of the CS in strong eluents, resulting column bleeding, and, in the worst case, destruction of the column material (Tang et al 2011;Padró and Keunchkarian 2018;Chankvetadze 2019;Fernandes et al 2021;Onishi et al 2022). One of the first immobilized, chemically robust CSPs were introduced by Okamoto et al as well, when they linked cellulose 3,5-dimethylphenyl carbamate-and 3,5-dichlorophenyl carbamate-type selectors onto 3-aminopropyl-functionalized silica gel by crosslinking with diisocyanates (Okamoto et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The success of an efficient enantioseparation is mainly determined by the chiral discriminative power of the CSP. Over the years, various types of CSPs have been described [ 127 , 128 , 129 ]; nevertheless, the development of new CSPs for LC continued to be an evolutionary subject, encompassing the preparation of new chiral selectors [ 130 ], the introduction of new chromatographic supports [ 131 ], and the application of different synthetic approaches for the preparation of CSPs [ 132 ]. Macrocyclic antibiotic-based, crown ether-based, and ligand exchange-type ( Figure 4 ) are the most-used CSPs for the enantiomeric separation of amino acids and primary amine-containing compounds [ 133 , 134 , 135 , 136 ].…”
Section: Liquid Chromatography Methods For Determination Of Absolute ...mentioning
confidence: 99%